Comparing Oncological and Perioperative Outcomes of Open versus Laparoscopic versus Robotic Radical Nephroureterectomy for the Treatment of Upper Tract Urothelial Carcinoma: A Multicenter, Multinational, Propensity Score-Matched Analysis - Grossmann, Nico C; Soria, Francesco; Juvet, Tristan; Potretzke, Aaron M; Djaladat, Hooman; Ghoreifi, Alireza; Kikuchi, Eiji; Mari, Andrea; Khene, Zine-Eddine; Fujita, Kazutoshi; Raman, Jay D; Breda, Alberto; et al. (Cancers, 2023)
OBJECTIVES: To identify correlates of survival and perioperative outcomes of upper tract urothelial carcinoma (UTUC) patients undergoing open (ORNU), laparoscopic (LRNU), and robotic (RRNU) radical nephroureterectomy (RNU). METHODS: We conducted a retrospective, multicenter study that included non-metastatic UTUC patients who underwent RNU between 1990-2020. Multiple imputation by chained equations was used to impute missing data. Patients were divided into three groups based on their surgical treatment and were adjusted by 1:1:1 propensity score matching (PSM). Survival outcomes per group were estimated for recurrence-free survival (RFS), bladder recurrence-free survival (BRFS), cancer-specific survival (CSS), and overall survival (OS). Perioperative outcomes: Intraoperative blood loss, hospital length of stay (LOS), and overall (OPC) and major postoperative complications (MPCs; defined as Clavien-Dindo > 3) were assessed between groups. RESULTS: Of the 2434 patients included, 756 remained after PSM with 252 in each group. The three groups had similar baseline clinicopathological characteristics. The median follow-up was 32 months. Kaplan-Meier and log-rank tests demonstrated similar RFS, CSS, and OS between groups. BRFS was found to be superior with ORNU. Using multivariable regression analyses, LRNU and RRNU were independently associated with worse BRFS (HR 1.66, 95% CI 1.22-2.28, p = 0.001 and HR 1.73, 95%CI 1.22-2.47, p = 0.002, respectively). LRNU and RRNU were associated with a significantly shorter LOS (beta -1.1, 95% CI -2.2-0.02, p = 0.047 and beta -6.1, 95% CI -7.2-5.0, p < 0.001, respectively) and fewer MPCs (OR 0.5, 95% CI 0.31-0.79, p = 0.003 and OR 0.27, 95% CI 0.16-0.46, p < 0.001, respectively). CONCLUSIONS: In this large international cohort, we demonstrated similar RFS, CSS, and OS among ORNU, LRNU, and RRNU. However, LRNU and RRNU were associated with significantly worse BRFS, but a shorter LOS and fewer MPCs.
Keywords: UTUC; RNU; surgical approach; transitional cell carcinoma; treatment outcomes